Pengembangan Profesi Guru Matematika Dalam Meningkatkan Kualitas Pembelajaran - Harry Soeprianto; Muhlis Muhlis; Kosim Kosim (Rengganis Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service is to provide motivation and socialization about the innovative work of teachers, in connection with the obligations of professional teachers. The observations show that Mathematics teachers still need more in-depth guidance on PTK (Class Action Research), starting from making proposals, implementation in the classroom, and how to make PTK reports. Likewise with the activity of writing scientific papers, it seems that more intensive training is needed.